2009
DOI: 10.1007/s10705-008-9243-6
|View full text |Cite
|
Sign up to set email alerts
|

Simulating phosphorus responses in annual crops using APSIM: model evaluation on contrasting soil types

Abstract: Crop simulation models have been used successfully to evaluate many systems and the impact of change on these systems, e.g. for climatic risk and the use of alternative management options, including the use of nitrogen fertilisers. However, for low input systems in tropical and subtropical regions where organic inputs rather than fertilisers are the predominant nutrient management option and other nutrients besides nitrogen (particular phosphorus) constrain crop growth, these models are not up to the task. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Kpongor (2007), Arthur (2009) and Adiku et al (2009). The influence of P nutrition on the growth of maize in Kenya was reported by Delve et al (2009), sorghum in semi-arid region in Ghana by MacCarthy et al (2009) and in wheat in India by Saha et al (2014). In this study, N was the most limiting soil nutrient as it is required in larger amounts than any other nutrient.…”
Section: Grain Yieldmentioning
confidence: 54%
See 1 more Smart Citation
“…Kpongor (2007), Arthur (2009) and Adiku et al (2009). The influence of P nutrition on the growth of maize in Kenya was reported by Delve et al (2009), sorghum in semi-arid region in Ghana by MacCarthy et al (2009) and in wheat in India by Saha et al (2014). In this study, N was the most limiting soil nutrient as it is required in larger amounts than any other nutrient.…”
Section: Grain Yieldmentioning
confidence: 54%
“…Thus, its deficiency becomes an important chemical factor restricting plant growth in soils. While N is the most limiting nutrient generally in soil, Delve et al (2009) has shown that deficiency of soil P reduces the efficiency of N use by crops.…”
Section: Introductionmentioning
confidence: 99%
“…This correlation, together with the greater stability of parameters other than A 0 , has allowed accurate modeling of leaf area per plant, only by knowing A 0 (Fournier and Andrieu, 1998;Valentinuz and Tollenaar, 2006;Boomsma et al, 2009). An alternative approach for modeling leaf area of P-and K-stressed crops could be linking A 0 with an indicator of stress, such as the P stress factor of the Agricultural Production Systems sIMulator (APSIM) model (Delve et al, 2009). An alternative approach for modeling leaf area of P-and K-stressed crops could be linking A 0 with an indicator of stress, such as the P stress factor of the Agricultural Production Systems sIMulator (APSIM) model (Delve et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Some existing models do account for P deficiency on maize growth, but much of the data come from field studies where there is variation due to air and soil temperature, soils, and, possibly, abiotic and biotic stresses (Mollier et al, 2008;Dzotsi et al, 2010;Delve et al, 2009). The data from this study would be useful for testing and parameterizing mechanistic algorithms to quantify P effects on maize photosynthesis and leaf growth.…”
Section: Implications For Modelingmentioning
confidence: 99%